2009
DOI: 10.3200/jach.58.1.56-63
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Stress, and Social Support Among Dental Students at a Historically Black College and University

Abstract: Stress and social support are associated with depressive symptoms among dental students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
71
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 50 publications
1
71
1
2
Order By: Relevance
“…For instance, Laurence et al (2009) observed that college students with more depressive symptoms perceived less social support and when symptoms of depression were controlled, social support did not predict perceived stress. In Barnes and Lightsey's (2005) study on African-American college students, social support did not predict perceived stress and did not have a moderator function on the relationship between racial discrimination and perceived stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Laurence et al (2009) observed that college students with more depressive symptoms perceived less social support and when symptoms of depression were controlled, social support did not predict perceived stress. In Barnes and Lightsey's (2005) study on African-American college students, social support did not predict perceived stress and did not have a moderator function on the relationship between racial discrimination and perceived stress.…”
mentioning
confidence: 99%
“…One of the important ways for students to cope with stress is social support (Chao, 2012;Laurence, Williams, & Eiland, 2009). Students naturally seek social support from friends and family when facing stress, and with this support it may be easier for them to cope with stress (Chao, 2012).…”
mentioning
confidence: 99%
“…5 Most studies exploring dental student stress have equated psychological well-being with the presence or absence of stress, or psychological disorders such as depression. [6][7][8] However, studies have also shown that there are multiple dimensions which contribute to a sense of positive psychological wellbeing. This body of knowledge suggests that positivelyfunctioning individuals establish goals, direction, and purpose, which give them a sense of meaning in life.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lack of social support is one of the independent risk factor for depression, meaning that the students who had low social support had higher depression. However, social support has buffering effects on depression among university students (Laurence, Williams, & Eiland, 2009;Oni, 2010 andChia &Graves, 2016).…”
Section: Introductionmentioning
confidence: 99%